Dual-stimuli responsive liposomes using pH- and temperature-sensitive polymers for controlled transdermal delivery. Issue 9 (3rd February 2017) - Yamazaki, Naoko; Sugimoto, Takumi; Fukushima, Mitsuhiro; Teranishi, Ryoma; Kotaka, Aki; Shinde, Chiharu; Kumei, Takayuki; Sumida, Yasushi; Munekata, Yuki; Maruyama, Kei-ichi; Yuba, Eiji; Harada, Atsushi; et al.
Abstract : The use of skin environment-sensitive liposomes for transdermal penetration is beneficial for improving cosmetic efficacy. Abstract : Recent development in transdermal drug delivery systems has led to an improvement of systemic and local efficacies. In the cosmetic field, liposomes have long been used as a container of cosmetic agents for their protection. Considering that these agents should be released from the liposomes at appropriate sites during their penetration into the skin, the use of skin environment-sensitive liposomes for transdermal penetration is beneficial for improving cosmetic efficacy. For this study, we prepared novel functional liposomes modified with methacrylate-based copolymers poly(MD- co -MAA- co -LT)s, which have sensitivity to both temperature and pH. Poly(MD- co -MAA- co -LT)s changed their water-solubility in response to both pH and temperature. Poly(MD- co -MAA- co -LT)-modified liposomes showed content release under conditions with acidic pH and temperatures higher than 35 °C, which correspond to endosome/lysosome environments of the melanocytes at the stratum basale of the skin. Polymer-modified liposomes were taken up efficiently by a murine melanoma cell line, B16–F10 cells, which delivered their contents into endosomes and cytosol. Polymer-modified liposomes could penetrate into the deep layers of skin models and reached the stratum basale. Results demonstrate that poly(MD- co -MAA- co -LT)-modified liposomes are promising as a system for delivering cosmetic agents to melanocytes.